2014
DOI: 10.5603/kp.a2014.0063
|View full text |Cite
|
Sign up to set email alerts
|

Coronary artery bypass grafting in patients over 80 years of age: a single-centre experience

Abstract: The most common concomitant conditions in the elderly patients undergoing cardiac surgery are hypertension and impaired renal function. The majority of operated patients already suffered a MI. AF and low cardiac output syndrome are the most common postoperative complications. Among patients above 80 years of age, operative mortality risk predicted using the EuroSCORE I and EuroSCORE II may be overestimated. Patient selection for cardiac surgery must be based on individual factors, taking into account the feasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…We observed the lowest O/E ratio in younger patients, with a value of 0.26 for patients <60 years and 0.42 for patients aged 60-69 years, while the ratio was 0.89 in patients ≥ 80 years. This was a surprising result, given that some smaller studies have indicated that EuroSCORE II overestimates mortality in octogenarians [9,10,13]. Hence, our hypothesis that EuroSCORE II would perform less well in octogenarians could not be con rmed, since the discrimination accuracy was only somewhat lower in older patients and the calibration was better.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…We observed the lowest O/E ratio in younger patients, with a value of 0.26 for patients <60 years and 0.42 for patients aged 60-69 years, while the ratio was 0.89 in patients ≥ 80 years. This was a surprising result, given that some smaller studies have indicated that EuroSCORE II overestimates mortality in octogenarians [9,10,13]. Hence, our hypothesis that EuroSCORE II would perform less well in octogenarians could not be con rmed, since the discrimination accuracy was only somewhat lower in older patients and the calibration was better.…”
Section: Discussionmentioning
confidence: 78%
“…Previous analyses of cardiac surgery risk scores, including EuroSCORE II, have noted that the scores overestimate the risk of death after CABG in octogenarians [9][10][11][12][13][14] and in high-risk patients [15,16]. However, most of these studies were performed in single-centre cohorts of limited size, and large contemporary population-based studies are lacking.…”
Section: Introductionmentioning
confidence: 99%
“…In the current study data were collected from 51 patients over the age of 80 years underwent coronary artery bypass graft surgery, their mean age was 81.7 years. The outcome of surgery in such an age depends on many factors that those patients could have them like hypertension in 76.5%, renal impairment in 62.7% [10].…”
Section: Discussionmentioning
confidence: 99%
“…Regardless of the presence of diabetes mellitus, single vessel coronary artery disease rather than multivessel disease could happen in younger age group, but was not the case in our study, sample was small in number and most of them were having diabetes. Studies reported that single vessel coronary artery disease occurs more frequently than multiple vessel involvement in younger ages, but the long-term prognosis in young patients having myocardial infarction is unfavorable [10].Supporting the fact that the outcome of the coronary artery bypass graft surgery is not favorable in young age patients, other study reported that the quality of life is significantly improved in patients underwent CABG surgery between the age of 60-69 years, also age group of 50-59 got similar outcome regarding the quality of life but to a lesser extent [11].…”
Section: Discussionmentioning
confidence: 99%
“…Routinely, in our study patients were evaluated using a scale of perioperative risk – the European System for Cardiac Operative Risk Evaluation (EuroSCORE) – and assessed by the Heart Team, and thus disqualified from operations. However, it was reported that in the group of octogenarians in 62.7% with impaired renal function preoperative mortality risk assessment determined on the basis of EuroSCORE I and EuroSCORE II may be overestimated [ 24 ]. Very common undertreatment can contribute to high and excess mortality of the oldest cardiorenal patients.…”
Section: Discussionmentioning
confidence: 99%